Parathyroid hormone receptors (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
The parathyroid hormone receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Parathyroid Hormone Receptors [47]) are family B G protein-coupled receptors. The parathyroid hormone (PTH)/parathyroid hormone-related peptide (PTHrP) receptor (PTH1 receptor) is activated by precursor-derived peptides: PTH (84 amino acids), and PTHrP (141 amino-acids) and related peptides (PTH-(1-34), PTHrP-(1-36)). The parathyroid hormone 2 receptor (PTH2 receptor) is activated by the precursor-derived peptide TIP39 (39 amino acids). [125I]PTH may be used to label both PTH1 and PTH2 receptors.